1993
DOI: 10.1037/0022-006x.61.6.984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of civilian trauma and posttraumatic stress disorder in a representative national sample of women.

Abstract: Prevalence of crime and noncrime civilian traumatic events, lifetime posttraumatic stress disorder (PTSD), and PTSD in the past 6 months were assessed in a sample of U.S. adult women (N = 4,008). Random digit-dial telephone methods were used to identify study participants. Structured telephone interviews for assessment of specific crime or other traumatic event history and PTSD were conducted by trained female interviewers. Lifetime exposure to any type of traumatic event was 69%, whereas exposure to crimes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

65
1,072
16
27

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,505 publications
(1,180 citation statements)
references
References 13 publications
65
1,072
16
27
Order By: Relevance
“…This may be due to the largely known offender assaults (83%) in this sample and a less powerful single-item, dichotomous measure of physical injury. These results support and extend past work showing the importance of perceived life threat in the etiology of PTSD symptomatology (Frazier et al, 1997;Kilpatrick et al, 1989;Resnick et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to the largely known offender assaults (83%) in this sample and a less powerful single-item, dichotomous measure of physical injury. These results support and extend past work showing the importance of perceived life threat in the etiology of PTSD symptomatology (Frazier et al, 1997;Kilpatrick et al, 1989;Resnick et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps the personally intrusive nature of rape is what makes it uniquely traumatic. Resnick, Kilpatrick, Dansky, Saunders, and Best (1993) studied a national sample of women and found that perceived life threat and physical injury were related to more PTSD, a diagnosis more common in rape victims than in victims of other traumatic life events. Kilpatrick et al (1989) reported that not only were individual factors of completed rape, physical injury, and life threat related to PTSD in female crime victims, but that these factors interacted synergistically in predicting PTSD risk.…”
mentioning
confidence: 99%
“…For example, studies in the United States have found that 30-84% of women who have experienced IPV suffer from PTSD (Cascardi, O'Leary, & Schlee, 1999;Kemp, Rawlings, & Green, 1991;Saunders, 1994;Yoshihama & Horrocks, 2003). These rates are much higher than the 10-14% rate of PTSD among women in the general population (Breslau & Davis, 1992;Breslau, Davis, Peterson, & Schultz, 1997;Kessler et al, 1995;Resnick, Kilpatrick, Dansky, Saunders, & Best, 1993).…”
Section: Ipv and Health Statusmentioning
confidence: 99%
“…Author manuscript; available in PMC 2010 December 20. Dansky, Saunders, & Best, 1993). PTSD includes symptoms of hyperarousal such as difficulties with sleep, feeling constantly "on guard" or hypervigilant, having a frequent and exaggerated startle response, and difficulties with focusing and concentration (American Psychiatric Association, 1994).…”
mentioning
confidence: 99%
“…Victimization experiences also increase the likelihood of having high levels of subsequent autonomic arousal. That is, victimization experiences frequently result in symptoms of posttraumatic stress disorder (PTSD; Resnick, Kilpatrick, Dansky, Saunders, & Best, 1993). PTSD includes symptoms of hyperarousal such as difficulties with sleep, feeling constantly "on guard" or hypervigilant, having a frequent and exaggerated startle response, and difficulties with focusing and concentration (American Psychiatric Association, 1994).…”
mentioning
confidence: 99%